1999
DOI: 10.1037/0735-7036.113.4.396
|View full text |Cite
|
Sign up to set email alerts
|

Scale-model comprehension by chimpanzees (Pan troglodytes).

Abstract: The ability of chimpanzees (Pan troglodytes) to recognize the correspondence between a scale model and its real-world referent was examined. In Experiments 1 and 2, an adult female and a young adult male watched as an experimenter hid a miniature model food in 1 of 4 sites in a scale model. Then, the chimpanzees were given the opportunity to find the real food item that had been hidden in the analogous location in the real room. The female performed significantly above chance, whereas the male performed at cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 13 publications
3
50
0
Order By: Relevance
“…We also found a main effect of language (F (1,44) ϭ 65.48, P Ͻ 0.001; Dutch: M ϭ 76.58, SD ϭ 8.1; Haiʈom: M ϭ 50.37, SD ϭ 14.4). Dutch participants outperformed Namibian participants, most likely because of more advanced formal schooling.…”
Section: Part 1: Cross-cultural Variationmentioning
confidence: 54%
See 1 more Smart Citation
“…We also found a main effect of language (F (1,44) ϭ 65.48, P Ͻ 0.001; Dutch: M ϭ 76.58, SD ϭ 8.1; Haiʈom: M ϭ 50.37, SD ϭ 14.4). Dutch participants outperformed Namibian participants, most likely because of more advanced formal schooling.…”
Section: Part 1: Cross-cultural Variationmentioning
confidence: 54%
“…However, none of these experiments, with infant or animal, used a strictly relational paradigm. Because prior research suggests that at least 4-year olds (11) and chimpanzees (44,45) can process relational information, we set out, in experiments 2 and 3, to determine whether there is a background preference for egocentric or allocentric coding of spatial relations through all great ape genera to see whether they share a cognitive ''wild type'' inherited from a common ancestor. Experiment 2.…”
Section: Part 2: Phylogenetic Inheritancementioning
confidence: 99%
“…After initial reports showed that apes [Menzel, 2001;Menzel and Kelley, 2002] and baboons [Vauclair, 1996] can use pictorial representations such as videos to solve retrieval tasks, more recent studies focused on the processes that underlie that ability. Kuhlmeier and collaborators showed that chimpanzees recognise objects and spatial correspondences between models or pictures and real situations [Kuhlmeier et al, 1999;Boysen, 2001, 2002]. Poss and Rochat [2003] showed that chimpanzees do not depend on direct processing of perceptual information or stimulus enhancement to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with chimpanzees have shown that some subjects are prone to using an alternative search strategy on the scale model task (Kuhlmeier & Boysen, 2001;Kuhlmeier, Boysen, & Mukobi, 1999). After witnessing the hiding event in the model, these chimpanzees simply searched the full-size space in a clockwise manner until ultimately finding the hidden item (a bottle of juice).…”
Section: This Experimentsmentioning
confidence: 99%